Effect of green tea extract and mouthwash without alcohol on Candida albicans biofilm on acrylic resin. (21st May 2014) - Antunes, Débora P.; Salvia, Ana Carolina R.D.; de Araújo, Rodrigo M.; Di Nicoló, Rebeca; Koga Ito, Cristiane Y.; de Araujo, Maria A.M.
Abstract : Objective: To evaluate the effect of aqueous extract of green tea and the oral antiseptic without alcohol, on Candida albicans biofilm formation to heat‐curing acrylic resin plates. Background: Candida is associated with oral candidiasis in poorly cleaned dentures. Material and methods: Standardised specimens of heat‐cured (Conv; n  = 30) or microwave‐cured acrylic resin (Mw; n  = 30) were obtained and divided into six groups ( n  = 10): G1 = Conv resin and green tea aqueous extract, G2 = Conv resin and mouthwash, G3 = control of Conv resin, G4 = Mw resin and green tea aqueous extract, G5 = Mw resin and mouthwash and G6 = control of Mw‐cured resin. The specimens were contaminated with 10 ml of Sabouraud dextrose broth inoculated with 0.1 ml of standard suspension containing 1 × 10 6  cells/ml of C. albicans and incubated for 24 h at 37°C. After this period, they were immersed in the aqueous extract or in mouthwash for 15 min. The control groups were treated with sterile distilled water. Aliquots of 0.1 ml were plated on Sabouraud dextrose agar and incubated at 37°C for 24 h. The numbers of colony‐forming units per test specimen (CFU/TS) were calculated, and the results statistically analysed by two‐wayanova and Tukey's tests (5%). Results: Statistically significant difference was observed for the aqueous extract groups (G1; 33.65%) and mouthwash (G2; 17.06%), when compared to control (G3; 100%), for Conv resin. For the Mw resin, there was significant difference between mouthwash (G5; 43.16%) and control (G6; 100%). Conclusion: The aqueous extract of green tea and mouthwash led to a reduction in the number of viable fungal cells in biofilm formed on acrylic resin.